Promoting healthy eating in early pregnancy in individuals at risk of gestational diabetes mellitus: does it improve glucose homeostasis? A study protocol for a randomized control trial - Bernier, Emilie; Plante, Anne-Sophie; Lemieux, Patricia; Robitaille, Julie; Lemieux, Simone; Desroches, Sophie; Bélanger-Gravel, Ariane; Maheux-Lacroix, Sarah; Weisnagel, S. John; Demers, Suzanne; Camirand Lemyre, Félix; Boulet, Mélanie; et al. (Frontiers in Nutrition, 2024)
Background: Healthy eating during pregnancy has favorable effects on glycemic control and is associated with a lower risk of gestational diabetes mellitus (GDM). According to Diabetes Canada, there is a need for an effective and acceptable intervention that could improve glucose homeostasis and support pregnant individuals at risk for GDM.Aims: This unicentric randomized controlled trial (RCT) aims to evaluate the effects of a nutritional intervention initiated early in pregnancy, on glucose homeostasis in 150 pregnant individuals at risk for GDM, compared to usual care.Methods: Population: 150 pregnant individuals ≥ 18 years old, at ≤ 14 weeks of pregnancy, and presenting ≥ 1 risk factor for GDM according to Diabetes Canada guidelines. Intervention: The nutritional intervention initiated in the first trimester is based on the health behavior change theory during pregnancy and on CFG recommendations. It includes 1) 4 individualized counseling sessions with a registered dietitian using motivational interviewing (12, 18, 24, and 30 weeks), with postinterview phone call follow-ups, aiming to develop and achieve S.M.A.R.T. nutritional objectives (specific, measurable, attainable, relevant, and time-bound); 2) 10 informative web capsules on healthy eating during pregnancy developed by our team and based on national guidelines, and 3) a virtual support community via a Facebook group. Control: Usual care (no nutritional intervention). Protocol: This RCT includes 3 on-site visits (10-14, 24-26, and 34-36 weeks) during which a 2-hour oral glucose tolerance test and blood samples are taken. At each trimester and 3 months postpartum, participants complete web-based questionnaires, including 3 validated 24-hour dietary recalls to assess their diet quality using the Healthy Eating Food Index 2019. Primary outcome: Change in fasting blood glucose (from the first to the third trimester) will be compared between groups. This study has been approved by the Ethics Committee of the Centre de recherche du CHU de Québec-Université Laval.Discussion: This RCT will determine whether a nutritional intervention initiated early in pregnancy can improve glucose homeostasis in individuals at risk for GDM and inform Canadian stakeholders on improving care trajectories and policies for pregnant individuals at risk for GDM.